Hubungan Brand Equity dengan Keputusan Pasien Memilih Rumah Sakit X Kota Depok - Ernica Theodora Waruwu; Ellynia Ellynia; Sarah Geltri Harahap (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Brand equity turns into a decisive element that affects patient choices. Patients are more likely to select hospitals with strong brand awareness, brand association, perceived quality, and brand loyalty, according. However, there is currently little research on the direct connection to the patient's decision-making process, particularly when it comes to hospitals.This study aims to determine the relationship between brand equity and patient decisions to choose Hospital X in Depok. This study uses a quantitative approach with a cross sectional design. The sample consisted of 131 outpatients selected using consevutive sampling technique and calculated with Gpower software. The independent variables include four brand equity indicators, namely brand awareness, brand association, perceived quality, and brand loyalty, while the dependent variable is the patient's decision. Data were collected through questionnaires and analyzed using the chi- square test. The results show that only brand loyalty is significantly related to patient decisions (p=0.009), while brand awareness, brand association, and perceived quality are not related but need to be improved through more effective marketing strategies. This study contributes to the management of RS X in developing branding strategies to increase patient attraction, especially by strengthening brand loyalty and improving aspects that are not yet optimal.